Phase Noise Influence in a Dual-Frequency Laser Phase-Shift Range Finder - Hongzhi Yang (IEEE Photonics Journal, 2018)
The influence of phase noise in a dual-frequency laser phase-shift range finder is theoretically and experimentally investigated. The proposed range finder is based on the use of a coherent dual-frequency laser and direct detection of the backscattered laser. The effects of laser phase noise and noise from an acousto-optic frequency shifter (AOFS) on the dual-frequency laser phase-shift range finder are analyzed. Expressions of the power spectral density and the phase noise of the dual-frequency laser beat note are deduced. In addition, we find that noise from the AOFS has a considerable impact on beat note noise conversion. The theoretical results can be used to estimate the influence of laser phase noise, noise induced by the AOFS and delay length in the dual-frequency laser range finder. An experiment involving the dual-frequency laser range finder is performed on outdoor targets at a distance of 200 m, and the phase jitter observed in the experiment is in good agreement with the model of beat note phase noise.